Endovascular Treatment of Giant Splenic Artery Aneurysm - Adenauer Marinho de Oliveira Góes Junior; Amanda Silva de Oliveira Góes; Paloma Cals de Albuquerque; Renato Menezes Palácios; Simone de Campos Vieira Abib (Case Reports in Surgery, 2012)
Introduction. Visceral artery aneurysms are uncommon. Among them, splenic artery is the most common (46–60%). Most splenic artery aneurysms are asymptomatic and diagnosed incidentally, but its rupture, potentially fatal, occurs in up to 8% of cases. Presentation of Case. A female patient, 64 years old, diagnosed with a giant aneurysm of the splenic artery (approximately 6.5 cm in diameter) was successfully submitted to endovascular treatment by stent graft implantation. Discussion. Symptomatic aneurysms and those larger than 2 cm represent some of the main indications for intervention. The treatment may be by laparotomy, laparoscopy, or endovascular techniques. Among the various endovascular methods discussed in this paper, there is stent graft implantation, a method still few reported in the literature. Conclusion. Although some authors still consider the endovascular approach as an exception to the treatment of SAA, in major specialized centers these techniques have been consolidated as the preferred choice, reserving the surgical approach in cases where this cannot be used. For being a less aggressive approach, it offers an opportunity of treatment to patients considered “high risk” for surgical treatment by laparotomy/laparoscopy.